Evaluation of human and animal disease reporting to assess knowledge, compliance, attitudes, and barriers & Analysis of access to essential public health services for Spanish-speaking residents of Riley County - Preczewski, Amanda S (My University, 2021)
Disease Reporting Project Abstract Whereas effective disease surveillance systems can protect the health of a community, ineffective systems—characterized by underreporting or delays in reporting—can make a community susceptible to dangerous outbreaks by masking disease spread throughout the population. The principles of disease reporting are consistent throughout the nation. Local and state health departments receive reports when healthcare providers diagnose or suspect certain diseases; the health departments then may conduct investigations or take other appropriate measures to mitigate disease spread. Though the principles are similar between states, each state and local health department may have slightly different disease reporting regulations, methods, and timelines and may designate different diseases as reportable. The Riley County Health department in the state of Kansas was receiving a very low number of disease reports in the spring of 2020 and suspected that local healthcare providers may be underreporting diseases. This project assessed disease reporting among human healthcare providers and veterinarians through written surveys. The surveys evaluated the knowledge of Kansas reporting regulations, measured attitudes toward reporting, identified barriers in the reporting process, and assessed self-reported compliance with existing regulation. Survey results suggested that a knowledge gap exists among human healthcare providers regarding disease reporting regulations. Additionally, results indicated a generally positive attitude toward reporting and a desire for more streamlined reporting procedures. Overall, this project’s small sample size and response rate limit its external validity. However, there are many ways to improve future research into Riley County disease reporting, including changing the target population to account for different practices’ reporting systems, changing the survey methodology from written surveys to in-person interviews, and using records from medical facilities and the health department to assess actual reporting compliance. Hispanic Outreach Project Abstract A person’s health is influenced by the accessibility of quality healthcare services and public health education in the community. When COVID-19 began to spread through Kansas in spring 2020, most of the messaging about COVID-19 and public health measures aimed at stopping disease spread was presented in English. The population of limited-English speakers in Kansas needed the same lifesaving messaging in their primary languages but often were not receiving it to the same degree that English speakers were. The Riley County Health Department wanted to improve outreach to the Spanish-speaking community members in order to improve the community’s overall access to essential public health services. This project surveyed Spanish-speaking/limited-English speaking community members throughout Riley County to identify their public health-related needs, barriers to accessing healthcare, attitudes toward Riley County Health Department, and awareness of Riley County Health Department services.
Keywords: Kansas; disease surveillance; health department; language; survey